Composição da carcaça e qualidade da carne de bovinos Nelore em terminação intensiva a pasto com diferentes aditivos - Nunes, Paloma Cristie de Araujo (2018)
The objective of this study was to evaluate the carcass composition and the meat quality of Nellore cattle intensively fed pasture with different additives. For the evaluation of the carcass composition, 28 non castrated Nellore males with an average age of 24 ± 2 months and initial average body weight of 480 ± 5 kg were used. The total area had 7.5 ha divided in 4 paddock with 1.88 ha each, formed with Urochloa brizantha cv. BRS Piatã, deferred grass lawn. The treatments consisted of additives in each supplement: supplement U (conventional formulation containing urea as a source of PNN), supplement UO (supplement U with partial replacement of urea by encapsulated urea as source of PNN - Optygen ®), supplement UOL UO added with yeast of the genus Saccharomyce cerevisae), supplement UOLP (UOL supplement with probiotic: Bacillus cereus, Enterococcus faecium, Lactobacillus acidophilus, Ruminobacter amylophilum, Ruminobacter succinogenes and Succinovibrio dextrinosolvens). Supplements, isonitrogenated, were formulated to contain 16% CP (% MS) and provided at a proportion of 1.75% PC / day, daily at 10 o ́clock. Twelve randomly selected bovines were used for the physical characteristics and meat quality. Samples of the tenderloin were collected between the 12th and 13th ribs, divided into three steaks-samples for analysis of period D0 and D14 of maturation, and centesimal composition. The UOL treatment was superior to the others for AOL and EGS, but for P8 it was superior only to the UO treatment. The use of ultrasonography to evaluate the carcass composition proved to be an effective tool. No difference (P<0.05) was observed for the evaluation parameters, physical and chemical composition of the carcass. The maturation period D14 was higher than D0 for cooking losses and color evaluation parameters. The additives used in the treatments do not alter the physical and chemical composition of the carcass, as well as the quality of the meat. The use of yeast as an additive in the bovine diet improves animal growth.